2009
DOI: 10.3209/saj.saj230103
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Novel Actinomycetes from Spider Materials

Abstract: To collect new kinds of microorganisms for screening of biologically active substances, we focused on spider materials (webs, cuticle, egg sac), previously uninvestigated sources of such organisms. Using a new method of pre-treatment with 70% ethanol, 1,159 strains of actinomycetes were isolated from 196 spider materials, based on their morphological features. Of these, 293 strains were identified as non-filamentous actinomycetes from their 16S rRNA gene sequences. More detailed examination indicated that 139 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…In recent years, with the progress in direct 16S rDNA sequencing techniques and the establishment of public-domain data- bases, 16S rDNA sequence comparison has been used successfully for simple identification at the genus or species level in ecological studies of actinomycetes (Wang et al, 1999;Muramatsu et al, 2003;Matsumoto, et al, 2006;Iwai, et al, 2009). In the present investigation, we demonstrated that 16S rDNA-based identification is an efficient method of identification, with 98.5% of 1,234 actinomycete isolates being identified to the genus level and 74.8% being identified to the species level.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, with the progress in direct 16S rDNA sequencing techniques and the establishment of public-domain data- bases, 16S rDNA sequence comparison has been used successfully for simple identification at the genus or species level in ecological studies of actinomycetes (Wang et al, 1999;Muramatsu et al, 2003;Matsumoto, et al, 2006;Iwai, et al, 2009). In the present investigation, we demonstrated that 16S rDNA-based identification is an efficient method of identification, with 98.5% of 1,234 actinomycete isolates being identified to the genus level and 74.8% being identified to the species level.…”
Section: Discussionmentioning
confidence: 99%
“…Actinobacteria associated with insect hosts are a very promising source of providing novel active small molecules that confer benefits to hosts [1][2][3][4]. The insect inner gut system is an important natural environment harboring diverse microbes that may produce bioactive substances.…”
mentioning
confidence: 99%
“…Secretary products of actinomycetes of rare ecosystems are meant to antagonistic to test pathogens are likely to be novel anti-mycobacterial compounds as they new to human pathogens. Analysis of 16S rDNA and the repetitive extragenic palindromic (REP)-PCR fingerprinting technique (25) have been suggested for characterization and classification of environmental actinomycetes. In recent years, with the progress in direct 16S rDNA sequencing techniques and the establishment of publicdomain data bases, 16S rDNA sequence comparison has been used successfully for simple identification at the genus or species level in ecological studies of actinomycetes (26).…”
Section: Characterization Of Active Strainmentioning
confidence: 99%